Controle de Fusarium verticillioides em sementes de milho com o óleo essencial de gengibre - Costa, Maria Luiza Nunes (2020)
The behavior of isolates of the species Fusarium verticillioides present in different corn-producing microregions, as well as the behavior of hybrids used in these regions in the presence of the above-mentioned pathogen whe ther in seeds, plant stems or crop remains, needs to be evaluated with the aim of better managing the diseases they cause. Alternative met hods with a smaller quantity of products harmful to the health have been employed to control diseases, reducing the use of pesticides and contributing to more sustainable agriculture. The objective of this study was to evaluate the control of F. verticillioides in corn seeds with essential oil (EO) of ginger, as well as the presence of this pathogen in the stem of plants originated from these seeds. Naturally infested seeds were treated with ginger essential oil at six concentrations (0, 1%, 2%, 3%, 4% and 5%). Evaluation included standard germination, seed health, emergence and emergence speed index in the substrate, and presence of pathogens in the seedlings. Experimental design was completely randomized for germination and health tests and in randomized blocks for the tests of emergence and disease incidence in the stems of corn seedlings. Ginger EO, at the concentrations 0 (zero), 1%, 2%, 3%, 4% and 5%, did not affect corn seed germinati on considering the evaluated hybrid and provided lower F. verticillioides incidence percentage at 1%, 4% and 5%. The oscillation in the germination pe rcentage of seeds treated with different concentrations of ginger EO was inversely proportional to the presence of the fungus F. verticillioides in the seeds. The emergence speed index of seeds treated with different concentrations of ginger EO was superior at the highest concentration. Ginger EO can be used in the treatment of corn seeds to control F. verticillioides at the evaluated concentrations.